A Feasibility study on the construction of socialized housing for informal settlers along the Metro Manila Esteros - Ang Dy Pay, Georgiana L.; Lim, Paola Marie Q.; Lozano, Maricor Arianne A.; Sanchez, Edlen Mari M. (Diliman, Quezon City College of Engineering, 2013)
The government is currently working on the relocation of informal settlers near the danger zones such as areas below sea level, areas with unstable land forms and areas near the waterways or esteros. The feasibility study of Solidarity Development Corporation (SDC) aims to help the government in their program by creating Socialized Housing along the Metro Manila's esteros. SDC provides an onsite relocation of the informal settlers creating housing that will provide safety in these danger zones and improve on the problems of clogging and pollution in the area. The market study stated that there was a deficit of 663,283 units of socialized housing for the years 2001-2011 as released by the Housing and Urban Development Coordinating Council (HUDCC). Currently, there are 60,130 informal settler families living along Metro Manila's esteros, 19,440 of which are living along the 8 major ones. Thus the group proposed to create socialized housing blocks for informal settlers who live along those esteros. Each unit of the housing block will be sold at PHP400,000 as mandated by the Housing and Land Use Regulatory Board (HLURB). More than just providing informal settlers with safer and more permanent housing units, SDC also aims to build sustainable communities in which relocated informal settlers can thrive in. Having established a great need for socialized housing, the market study moved on to identify the Philippine government as the primary market for the project. The company will prioritize approaching the Department of Interior and Local Government (DILG) mainly because of how relevant the issue of on-site informal settler relocation is to them. The company will also be approaching the different Local Government Units (LGUs) as they are mandated by the DILG to have their own relocation programs. This project will also pose various individual benefits to the LGUs such as beautification of the cities. HUDCC will also be approached, as they are the main coordinating council of the country's housing sector, but this will only be done after the 2016 elections. Before that, a substantial amount of units can be built by the DILG and the LGUs. Sales forecasts were made and a targeted total number of 7,200 units to be built were set. Marketing costs were also established in the market study. The technical study finalized the design for the project, setting one housing block to consist of 3 floors of 16 residential units each with 18 sq.m of liveable area. Each floor will have a communal kitchen, a study room and a garbage room. One module will be composed of two housing blocks running along both sides of the esteros. On the ground floor will be a void deck, primarily to be used as a means for the residents to gather and interact with each other, while at the same time, elevating all the units up one floor in order to protect them from possible floods. The technical study also determined the two phases of the project: the pre-construction phase and the construction phase. The pre-construction phase includes necessary permit filing, contract signing, hiring of laborers and procuring of equipment and materials. The construction phase is the actual building of the housing units. Pre-construction period will take up 12 months while the construction period will last 20 months. The company plans to build divide the 7,200 units into 75 modules. 1 module will take up to 4 months to complete effectively allowing one crew to produce 5 modules during the construction period. Materials and equipment were discovered to be easily acquired as they are available from various suppliers in the Metro Manila area. It was also determined that it would be cheaper to purchase the equipment needed as opposed to renting them. Total start-up and operating expenses were calculated to be PHP2.29 Billion. In order to sustain operations during the pre-construction period, both equity and debt financing will be utilized. In the first month of pre-construction phase, SDC will produce PHP4,000,000 in paid-up capital. On the third month, bank loan of PHP20,000,000 at 15% annual interest rate will be availed. All cash transactions directly related to the socialized housing project are eligible for tax exemption as per Republic Act 7279 or the Urban Development and Housing Act. This states that private developers engaged in socialized housing products are exempted from project-related income taxes and other such taxes. Using an interest rate of 20%, the Net Present Value of the project is PHP383,966,996.51 which shows that the project is profitable. Financial projections made in the financial study were proven to have shown positive cash flows and net income making the project financially feasible. All four parts of the feasibility study showed positive results. There is a solid market for the product and it is technically feasible to create the project. The project is also financially stable and is greatly beneficial in terms of socio-economic profitability. Overall, the activities of Solidarity Development Corporation are feasible.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Participatory monitoring and evaluation (Project management); Housing; Public housing